1987
DOI: 10.1037/0735-7044.101.4.465
|View full text |Cite
|
Sign up to set email alerts
|

Nutrients that modify the speed of internal clock and memory storage processes.

Abstract: Two experiments assessed the effects of nutrients on timing behavior by rats. The nutrients were laced with saccharin and given to rats as a snack before training on a 20-s peak-interval procedure. The primary component of the snacks for four groups of 10 rats was lecithin (phosphatidylcholine), protein (casein), carbohydrate (sucrose), or a nonnutrient (saccharin). The primary measure of behavior was the time of the rat's highest response rate during a trial (peak time), which represented the interval during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
47
1

Year Published

1988
1988
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(56 citation statements)
references
References 35 publications
8
47
1
Order By: Relevance
“…In this respect the present finding is consistent with our previous observation of an increased coefficient of variation of IRTs under an IRT >t schedule, another "immediate" timing procedure (Wogar et al 1992(Wogar et al , 1993b. Meck and Church (1987b) reported that peak time was significantly reduced following acute exposure to a dietary regimen that is believed to increase the availability of free tryptophan. These authors attributed this effect to enhanced central 5HTergic function, and offered an explanation of the effect in terms of their cognitive model of the "internal clock" .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In this respect the present finding is consistent with our previous observation of an increased coefficient of variation of IRTs under an IRT >t schedule, another "immediate" timing procedure (Wogar et al 1992(Wogar et al , 1993b. Meck and Church (1987b) reported that peak time was significantly reduced following acute exposure to a dietary regimen that is believed to increase the availability of free tryptophan. These authors attributed this effect to enhanced central 5HTergic function, and offered an explanation of the effect in terms of their cognitive model of the "internal clock" .…”
Section: Discussionsupporting
confidence: 94%
“…Their model postulates a "pacemaker" that emits pulses, and an "accumulator" that counts these pulses; in judging a time interval (for example, the interval between trial onset and reinforcer availability), the organism compares the current "pulse-count" with "pulse-counts" previously stored in memory, and, depending upon the degree of agreement between the current and stored "counts", "decides" whether to emit a response (see also Meck and Church 1987a;Gibbon and Church 1990). Meck and Church (1987b) proposed that 5HTergic function may normally help to regulate the pacemaker, and that the increase in peak time seen in their experiment reflected a slowing of the pacemaker brought about by enhanced 5HTergic transmission. It should be noted, however, that according to Meck and Church's (1987b) model, a change in peak time is only expected to occur following acute exposure to an intervention that alters pacemaker activity; during chronic exposure to such an intervention, it is postulated, revised "pulse-counts" based on the new time-base become stored in memory, allowing peak time to revert to its original value (see also Meck et al 1984).…”
Section: Discussionmentioning
confidence: 96%
“…The neuropharmacological model maintains that drugs and other compounds that increase or decrease acetylcholine levels should produce gradual overestimation and underestimation of time, respectively. Although some studies have found support for the role of acetylcholine in timing (e.g., Meck, 1983;Meck & Angell, 1992;Meck & Church, 1987a, 1987b, a recent study did not (Odum, 2002).…”
Section: Discussionmentioning
confidence: 97%
“…Lesioning of the frontal cortex in rats leads to a shift in response gradients that suggests that reference durations are remembered as too long, and choline antagonists have a similar (though reversible) effect (Meck, 1983(Meck, , 1994Meck & Church, 1987;Meck et al, 1986). The choline system is known to be affected by aging (Bartus, Dean, Beer, & Lippa, 1982;Bartus et al, 1987).…”
Section: Discussionmentioning
confidence: 99%